The Critical Role of Local Wisdom In Supporting Water Sustainability and Climate Crisis Mitigation - Yunike Sulistyosari; Paulus Robert Tuerah; Rahmania Rahman (Keraton: Journal of History Education and Culture, 2025)
The escalating global environmental crises, particularly water scarcity and the pervasive impacts of climate change, necessitate a re-evaluation of conventional management strategies and an urgent search for sustainable solutions. This systematic literature review investigates the profound, yet often overlooked, contributions of local wisdom and Indigenous Knowledge to achieving water sustainability and mitigating the effects of climate crises. Local wisdom, defined as basic knowledge gained from living in balance with nature, accumulated and passed on through generations, integrates the body, spirit, and environment, emphasizing respect for ecological balance and community well-being (Musi et al., 2022). The purpose of this study is to systematically review and synthesize existing academic literature to elucidate how these traditional knowledge systems provide effective and culturally appropriate strategies for environmental resilience. Employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology (Abas et al., 2022; Dorji et al., 2024; Sahani et al., 2025), this review analyzes a comprehensive body of research to identify key themes and empirical evidence. Findings highlight the efficacy of local wisdom in various aspects, including traditional water conservation practices (e.g., rainwater harvesting, terracing, wetland management) and enhancing climate resilience through adaptive farming techniques and weather prediction (Sahani et al., 2025). Furthermore, indigenous knowledge systems contribute significantly to nature conservation, sustainable water management, and climate change adaptation efforts (Abas et al., 2022; Zvobgo et al., 2022). These insights underscore the critical need to integrate local and Indigenous Knowledge with modern scientific approaches to foster robust, sustainable, and equitable responses to contemporary environmental challenges. The implications of this study suggest that recognizing and leveraging local wisdom can provide innovative and context-specific pathways toward global water security and climate stability